MUC554 : New music / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course focuses on Western art music of the 20th and 21st century. Students listen, analyze and discuss to selected compositions by new music composers. Starts with general overview from transitional period in the late 19th century until mid 20th century and then continue onwards until early of 21st century. In the process they will learn samples of 20th century compositional techniques such as 12 tones serial method (serial composition), indeterminacy, chance and ‘aleatoric’ compositions, and improvisation, graphic and text scores, minimalism, concrete and electronic/computer music, and selected samples of non Western composers. Students will learn samples of new music compositional notations, forms, structures, terminologies, performance signs and mode of expression and apply these to their own compositional works.